New Trypanosoma brucei acting derivatives incorporating 1-(4-phenyl)adamantane and 1-(4-phenoxyphenyl)adamantane - Stavropoulou, Konstantina; Kaimaki, Angeliki; Nikolaou, Maria; Brown, Ana K.; Tsotinis, Andrew; Taylor, Martin C.; Kelly, John M.; Papanastasiou, Ioannis (RSC Medicinal Chemistry, 2025)
New 1-(4-phenyl)adamantane and 1-(4-phenoxyphenyl)adamantane derivatives, functionalised with imidazolines, linear amidines, aminoguanylhydrazone and thiosemicarbazone moieties present activity against T. brucei .